Amba in Gender Study Perspective - I Wayan Nuriarta; Renata Lusilaora Siringo Ringo (Institut Seni Indonesia Denpasar, 2022)
Gender studies are used as a tool to examine gender issues, especially in analyzing gender inequality in society. There are three gender assessment criteria used to re-read the story of the Amba character in the Mahabharata comic by Gun Gun. The three criteria are (1) Activity Analysis, (2) Control/Dominance Analysis, and (3) Impact Analysis. Amba is one of the king's daughters who gets unfair treatment in her life. Regarding this treatment as a symbolic fact, it is important to re-read the character and life story of Dewi Amba with gender studies. This study uses a descriptive design with qualitative methods. The type of data in this study is qualitative data in the form of visual text and verbal text of the Mahabharata comic by Gun Gun in the story of Kutukan Dewi Amba (Dewi Amba's Curse). Data analysis was carried out by identifying and describing the data, classifying the data, analyzing it based on the gender study criteria that had been formulated, and drawing conclusions. The results show that in this context the dominant stereotype that women are weak and men are strong is deeply emphasized. The woman who is described as Dewi Amba is the party who is most unfairly treated due to male domination in her life.